2017
DOI: 10.5194/bg-14-45-2017
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an ozone deposition scheme for coupling to a terrestrial biosphere model

Abstract: Abstract. Ozone (O 3 ) is a toxic air pollutant that can damage plant leaves and substantially affect the plant's gross primary production (GPP) and health. Realistic estimates of the effects of tropospheric anthropogenic O 3 on GPP are thus potentially important to assess the strength of the terrestrial biosphere as a carbon sink. To better understand the impact of ozone damage on the terrestrial carbon cycle, we developed a module to estimate O 3 uptake and damage of plants for a state-of-the-art global ter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(88 citation statements)
references
References 110 publications
(131 reference statements)
0
83
0
Order By: Relevance
“…Globally, concentrations of O 3 predicted for 2100 reduced GPP by 14 to 23 % using a former parameterisation of O 3 sensitivity in JULES (Sitch et al, 2007). The recent study by Franz et al (2017) showed mean GPP declined by 4.7 % over the period 2001 to 2010 using the OCN model over the same European domain and using the same O 3 forcing produced by EMEP MSC-W as used in this study. Our estimates of changes in present-day GPP and NPP are at the lower end of previously modelled estimates.…”
Section: Comparison Of Modelled Estimates Of O 3 Damagementioning
confidence: 56%
See 3 more Smart Citations
“…Globally, concentrations of O 3 predicted for 2100 reduced GPP by 14 to 23 % using a former parameterisation of O 3 sensitivity in JULES (Sitch et al, 2007). The recent study by Franz et al (2017) showed mean GPP declined by 4.7 % over the period 2001 to 2010 using the OCN model over the same European domain and using the same O 3 forcing produced by EMEP MSC-W as used in this study. Our estimates of changes in present-day GPP and NPP are at the lower end of previously modelled estimates.…”
Section: Comparison Of Modelled Estimates Of O 3 Damagementioning
confidence: 56%
“…A similar approach is taken by Franz et al (2017) in the OCN model; however plant O 3 damage is a function of accumulated O 3 exposure over time. In JULES, plant O 3 damage is instantaneous because the impact of cumulative O 3 exposure on plant productivity has already been calibrated with observations (described below).…”
Section: Representation Of O 3 Effects In Julesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a paucity of long-term measurements of O 3 deposition over forest vegetation (Mikkelsen et al, 2004;Fares et al, 2010;Rannik et al, 2012) but long-term series are important to study the O 3 dry deposition processes in different climatic and environmental conditions. In addition, new findings regarding O 3 dry deposition schemes must be incorporated in climate models, to assess effects of future climate scenarios on O 3 removal and to predict future vegetative exposure to O 3 under climate change and projected precursor emission reductions (Klingberg et al, 2014;Mills et al, 2016;Zhang et al, 2016;Franz et al, 2017;Sicard et al, 2017). Ozone induced damage may disrupt the hydrological cycle and key biogeochemical cycles, including those of carbon and nitrogen (Schreuder et al, 2001;Paoletti and Grulke, 2010;de Vries et al, 2014;Hoshika et al, 2015;Franz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%